Characterization of pneumococcal meningitis before and after introduction of 13-valent pneumococcal conjugate vaccine in Niger, 2010–2018 - Ousmane, Sani; Kobayashi, Miwako; Seidou, Issaka; Issaka, Bassira; Sharpley, Sable; Farrar, Jennifer L.; Whitney, Cynthia G.; Ouattara, Mahamoudou (Vaccine, 2020)
Pneumococcal meningitis in the African meningitis belt is primarily caused by Streptococcus pneumoniae serotype 1, a serotype contained in the 13-valent pneumococcal conjugate vaccine (PCV13). In 2014, Niger introduced PCV13 with doses given at 6, 10, and 14 weeks of age. We leveraged existing meningitis surveillance data to describe pneumococcal meningitis trends in Niger. As a national reference laboratory for meningitis, Centre de Recherche Médicale et Sanitaire (CERMES) receives cerebrospinal fluid specimens from suspected bacterial meningitis cases and performs confirmatory testing for an etiology by culture or polymerase chain reaction (PCR). Specimens with S. pneumoniae detection during 2010–2018 were sent to the Centers for Disease Control and Prevention for serotyping by sequential triplex real-time PCR. Specimens that were non-typeable by real-time PCR underwent serotyping by conventional multiplex PCR. We tested differences in the distribution of pneumococcal serotypes before (2010–2012) and after (2016–2018) PCV13 introduction. During January 2010 to December 2018, CERMES received 16,155 specimens; 5,651 (35%) had bacterial etiology confirmed. S. pneumoniae accounted for 13.2% (744/5,651); 53.1% (395/744) were serotyped. During 2010–12, PCV13-associated serotypes (VT) constituted three-fourths of serotyped pneumococcus-positive specimens; this proportion declined in all age groups in 2016–18, most substantially in children aged < 5 years (74.0% to 28.1%; P < 0.05). Among persons aged ≥ 5 years, VT constituted > 50% of pneumococcal meningitis after PCV13 introduction; serotype 1 remained the most common VT among persons aged ≥ 5 years, but not among those < 5 years. VT as a group caused a smaller proportion of reported pneumococcal meningitis cases after PCV13 introduction in Niger. Serotype 1, however, remains the major cause of pneumococcal meningitis in older children and adults. Different vaccination strategies, such as changing the infant vaccination schedule or extending vaccine coverage to older children and adults, are needed, in addition to stronger surveillance.